What can the Welsh school music sector learn from the community music movement?. Issue 1 (1st April 2021) - Smith, Rob
This article draws on theories of creative development articulated by Sawyer and Green as well as reflecting upon data from case studies of projects run in Wales with community ensembles Wonderbrass, South Wales Intercultural Community Arts and London-based Kinetica Bloco. It proposes a model of learning for music education in Wales that promotes active creative participation and fosters the speaking of a musical language rather than simply the reading of it. In the context of Welsh Government's recent education review, the article advocates a music policy of creative engagement, with musical materials that go beyond the pedagogy of imitation. Here I propose a creative engagement method that empowers participants to interact with musical materials by creating their own musical statements within a musical style or language, whether through extemporization, improvisation or composition.